Outcome of Covid-19 Patients Admitted in Emergency Department of Karnali Academy of Health Sciences, Teaching Hospital - Krishna Gupta, Tula; Bhattarai, Kushal; Pal, Anusmriti; Kasaudhan, Smriti Mayur; Manandhar, Nilu (Journal of College of Medical Sciences-Nepal, 2023)
Introduction COVID-19, a global health problem, was first identified in the Hubei province, China. While various clinical features of the diseases have been documented, the complete clinical profile is yet to be understood. The purpose of this study is to evaluate the outcome of Covid-19 after admission in the emergency of KAHS during the year 2021January – 2022 January. Methods This is a hospital-based, retrospective, observational study done in the emergency department of Karnali Academy of Health Sciences (KAHS), Jumla. The data was taken from the registry, including the record files of patients with Covid-19 admitted in the hospital from 2020 January to 2021 January. The retrieved data was initially entered in an Excel sheet followed by its analysis. We carried out Kaplan Meier survival distribution analysis to determine the survival probability and predictors of Covid-19. Results Of the 516 Covid-19 positive patients who were admitted in the hospital, 53.5% were males. For the total patients, the mean duration of hospital stay was 8.02±5.32 days with the proportion of patients who died during treatment being 3.7% (n=19). As described by the Kaplan-Meier curve and the accompanying survival table, the mean survival time of the overall patients was 36.74 days (95% CI=35.6–37.8). Moreover, the cumulative survival rate was seen prominently decreased for older patients and those admitted in the intensive care unit and/or ventilator. Conclusion The increased mortality rates seen in the older patients and those admitted in critical care setting clearly calls for the importance of proper and timely intervention.